HEMODYNAMIC AND BIOELECTRICAL PROPERTIES OF THE BRAIN IN YOUNGER ADULTS WITH NONSTABLE BLOOD PRESSURE - G. G. Efremushkin; T. V. Filippova; A. G. Kharlova; V. V. Dekhar (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To study macro- and microhemodynamics and bioelectrical properties of the brain in younger adults with nonstable blood pressure (BP).Material and methods. A population of 79 adults at the age of 19–24 (average 19,9±0,9 years) was examined. According to the BP level they were divided into two groups: 1–46 (58,5%) with stable normal BP (SNBP), and 2–33 (41,5%) with high normal BP inside the range for 1st level arterial hypertension, whose BP was not stable (UsBP), but changing from normal values to 1st level hypertension. All patients undergone investigation of brachiocephal and intracerebral vessels with blood flow velocity measurement along the vessel direction, the blood sectional volumetric flow and specific kinetic energy. Microcirculation in the brain was measured by rheoencephalography including parameters of the velocity, time and volumetric parameters. Bioelectricity studied by electroencephalography.Results. In patients with UsBP we found the increase of blood flow velocity, blood volume and specific kinetic flow energy in vertebral and general carotid arteries as in basilar and middle cerebral arteries to. In the area of microcirculation in patients with UsBP the blood filling of frontal lobes was decreased comparing to SNBP patients in whom blood filling showed “mosaic” pattern. In UsBP patients we found changes of bioelectrical activity which are related to the functioning of cortical and subcortical portions of the brain.Conclusion. In younger patients with UsBP there is developed discirculatory encephalopathy with damage of cortex and subcortical portions of the brain due to impaired hemodynamic and microcirculation.